Analisis Pengaruh Green Manufacturing terhadap Firm Performance pada Sektor Industri Manufaktur Alas Kaki - Robbi, Anis Iman Illahi; Nuryanto, Uli Wildan; Handayani, Yolla Sukma (Universitas Serang Raya, 2025)
The footwear industry in Indonesia faces major challenges in maintaining competitiveness and operational efficiency, especially amid global pressure to implement sustainability principles. As one of the approaches that prioritizes efficient and environmentally friendly resource management, green manufacturing is a major concern for companies in improving performance. This study aims to analyze the influence of green manufacturing implementation on company performance in the footwear industry. The data analysis technique used in this study is SEM (Structural Equation Modelling) with the LISREL 8.80 program. Data was collected through a questionnaire distributed to managers and operational staff in several footwear companies in Tangerang Regency to test the relationship between green manufacturing variables and company performance measured based on green design, green process, and green procurement. The study results show that implementing green manufacturing has a positive and significant influence on the performance of footwear industry companies. Applying environmentally friendly technology and using energy and raw materials efficiently has been proven to increase productivity and reduce operational costs. In addition, companies that adopt green manufacturing also recorded improved product quality that is more consistent and in accordance with international standards. This study concludes that applying green manufacturing principles can be an effective strategy to improve the performance of footwear industry companies in terms of productivity, cost efficiency, and product quality. Therefore, companies in this sector are advised to integrate green manufacturing into their production processes to support sustainability and competitiveness in the global market.